2020
DOI: 10.1177/0363546520939897
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic and Symptomatic Knee Osteoarthritis 32 to 37 Years After Acute Anterior Cruciate Ligament Rupture

Abstract: Background: The long-term prevalence of knee osteoarthritis (OA) after anterior cruciate ligament (ACL) injury is unknown, especially in patients without a history of ACL surgery. Purpose: To (1) describe the prevalence of radiographic OA, symptomatic OA, and knee replacement surgery 32 to 37 years after acute ACL injury and to (2) compare the prevalence of radiographic OA, symptomatic OA, and knee symptoms between patients allocated to early ACL surgery or no ACL surgery and patients who crossed over to ACL s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 51 publications
(114 reference statements)
0
41
1
Order By: Relevance
“…9,13 Studies with long-term follow-up have also suggested that knee-related quality of life and risk for symptomatic knee osteoarthritis do not differ between ACLR and non-ACLR treatment. 11,12,21,31 This emphasizes the importance of making the right decision for the right patient to minimize the risk of subsequent injuries and to avoid unnecessary surgery. Treatment decisions after ACL injury seem to be made with consideration of existing guidelines, 4,26,29 and follow-ups with patients from the present study will show if the decisions were appropriate regarding satisfaction with knee function, activity level, and risk for new injuries for each patient.…”
Section: Discussionmentioning
confidence: 99%
“…9,13 Studies with long-term follow-up have also suggested that knee-related quality of life and risk for symptomatic knee osteoarthritis do not differ between ACLR and non-ACLR treatment. 11,12,21,31 This emphasizes the importance of making the right decision for the right patient to minimize the risk of subsequent injuries and to avoid unnecessary surgery. Treatment decisions after ACL injury seem to be made with consideration of existing guidelines, 4,26,29 and follow-ups with patients from the present study will show if the decisions were appropriate regarding satisfaction with knee function, activity level, and risk for new injuries for each patient.…”
Section: Discussionmentioning
confidence: 99%
“…9 This is expected since not all participants in our cohort had knee osteoarthritis at the 32-to 37-year follow-up. 18 Of the 153 who underwent knee radiographs, 62% had radiographic tibiofemoral osteoarthritis, and 35% had patellofemoral osteoarthritis. 18 Surprisingly, KOOS Pain and Symptoms scores were similar to those reported by individuals with an acute ACL injury and similar or worse than KOOS subscale scores reported within the first year after ACLR.…”
Section: Patient-reported Outcomes 32 To 37 Years After Acl Injurymentioning
confidence: 99%
“…18 Of the 153 who underwent knee radiographs, 62% had radiographic tibiofemoral osteoarthritis, and 35% had patellofemoral osteoarthritis. 18 Surprisingly, KOOS Pain and Symptoms scores were similar to those reported by individuals with an acute ACL injury and similar or worse than KOOS subscale scores reported within the first year after ACLR. 9,19 Additionally, KOOS scores were worse in individuals 5 to 16 years after ACLR 13 and in individuals with ACL-deficient knees 5 to 23 years after ACL injury.…”
Section: Patient-reported Outcomes 32 To 37 Years After Acl Injurymentioning
confidence: 99%
“…Non-operative management of torn anterior cruciate ligament (ACL) can be associated with the development of osteoarthritis (OA) [1], especially when there are concomitant meniscal or multiligament injuries [2], and they are more frequently observed as long-term sequelae in athletes [3,4]. There is an ongoing debate about whether the risk of developing OA in conservatively treated ACL tears is higher than after ACL reconstruction due to the resulting rotational instability, which can lead to higher meniscal and cartilage shear forces [5][6][7].…”
Section: Introductionmentioning
confidence: 99%